The Effect of Government Expenditure on Education on Economic Growth In the province of Central Sulawesi - Andi Herman Jaya (Jurnal Mantik, 2019)
The purpose of this study was to determine the effect of government spending on education on economic growth in Central Sulawesi Province. The data used in this study is data on government spending on education and economic growth in Central Sulawesi in 2010-2020. The data analysis technique used in this research is simple linear regression analysis. The software used to perform the analysis is IBM SPSS Version 22.00. The results of the analysis show that government spending on education has a significant effect on economic growth with a positive relationship direction, meaning that if government spending on education increases, economic growth in Central Sulawesi Province in 2010-2020 also increases.